If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 4 = 2(4 + -1x) Reorder the terms: 4 + -6x = 2(4 + -1x) 4 + -6x = (4 * 2 + -1x * 2) 4 + -6x = (8 + -2x) Solving 4 + -6x = 8 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4 + -6x + 2x = 8 + -2x + 2x Combine like terms: -6x + 2x = -4x 4 + -4x = 8 + -2x + 2x Combine like terms: -2x + 2x = 0 4 + -4x = 8 + 0 4 + -4x = 8 Add '-4' to each side of the equation. 4 + -4 + -4x = 8 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = 8 + -4 -4x = 8 + -4 Combine like terms: 8 + -4 = 4 -4x = 4 Divide each side by '-4'. x = -1 Simplifying x = -1
| 5x-2x-8=13 | | 3x^2+5y-6=0 | | sen(5x)-sen(3x)-sen(x)=0 | | 6s+-6=s+14 | | -2(a-8)=36 | | 16(1/2x)4 | | 3m^3=27m^3 | | T=4033/33000*.021 | | 4-3+10=101 | | 0.9ln(10000-0.01D)+0.1ln(10000-7000+0.99D)= | | T=4033/33000*2.1 | | 0.07x=1810 | | 0.07=1710 | | 2xyz/w= | | 0.1ln(0.1x)+0.9(0.9x)= | | 0.07x=1710 | | 7(n-5)-(4-3n)=9 | | z+(-22)=96 | | 3x+6+3(4x+5)= | | 4.3q-3.2-3.9q=0.6q-5.8 | | Log(w^2-4)-log(w-2)=2 | | 1.9-5.7-5.8q=-4.9q-2.6 | | T=0.4x | | 7e^4x-3=9 | | -10=9x^2 | | 20w^2+19w+3=0 | | .33/3=6/t | | 8-3+10x=66 | | 2tanx-6=0 | | 9h^2-64=0 | | 3x-1/5=2/5 | | y=10+9x^2 |